Conformity of the Waste Bank Accounting System with SAK-EMKM in Kendal City - Jatmika, Surya; Wijayanti, Alya Adita Nur; Sari, Dhany Efita; Laksmi, Azarin Carissa Putri (Jayapangus Press, 2025)
The financial management of waste banks plays a crucial role in ensuring their sustainability and accountability. However, many waste banks, including the Langenharjo Waste Bank, face challenges in implementing accounting systems that comply with financial reporting standards. This study aimed to describe the accounting system implementation in Langenharjo Waste Bank and its conformity with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK-EMKM), from its transaction recording system to the final financial statements. This qualitative research applied a case study design with research subjects involving the chairman, the treasurer, and two staff. The data were collected through interviews, observations, and documentation; validated using source and method triangulation; and analyzed using interactive analysis. The results showed that the accounting system implementation in Langenharjo Waste Bank had been conducted regularly and manually in two ways: listing the garbages, the customers and their savings, and the particular journals; and reporting the profit and the loss. The results also indicated that the accounting system implementation at Langenharjo Waste Bank had not conformed with the SAK-EMKM. The main reason was the need for more accounting management knowledge. Some changes needed at the recording stage were making a general journal, completing the classification, and summarizing phases by making ledgers and trial balances. At the reporting stage, it was necessary to prepare the financial position report and notes on financial statements to improve the accounting system at Langenharjo Waste Bank.